Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Siswa Slta Se Kota Serang - Deni Rusli; Ahmad Wahyudin; Lesi Lesiani; Hayumi; Arip Arizal Mustahidin (CV. Creative Tugu Pena, 2026)
This research aims to determine the relationship between the role of Islamic Religious Education Teachers (PAI) in shaping the religious character of high school students throughout Serang City. The approach used is quantitative with survey methods. The research sample consisted of 300 respondents who were high school students in Serang City. The data collection technique uses a questionnaire with a Likert scale which has been tested for validity and reliability. Data analysis was carried out using the SPSS program through the Kolmogorov-Smirnov normality test and Spearman's rho correlation test. The research results showed that the data was not normally distributed with a significance value of 0.000 (<0.05), so the analysis continued using non-parametric statistics. The results of the Spearman correlation test show a correlation coefficient value of 0.017 with a significance value of 0.767 (>0.05). This shows that there is no significant relationship between the role of PAI teachers and students' religious character. Thus, the research hypothesis which states that there is a relationship between the two variables cannot be accepted. These findings indicate that the formation of students' religious character is not only influenced by the role of PAI teachers, but also by other factors such as family environment, peers, school culture, and the influence of social media.